COMPARTIMENTOS DA MATÉRIA ORGÂNICA DO SOLO COMO INDICADORES DO SEQÜESTRO DE CARBONO EM SISTEMA PLANTIO DIRETO DE LONGA DURAÇÃO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
Decrease in soil organic carbon (SOC) content of the surface layer into deeper layers indicates the occurrence of the stratification in the profile due to continuous C addition of crop residues enriching the soil surface layer. The objective of this study was: in Chapter 3 the relationship of stratification (RE) of C of the soil organic matter (SOM) pools can be an indicator of C sequestration in no-tillage soils? In the chapter 4 the tensile strength of aggregates is affected by the C content of Pedosequence of Latosol with medium and clay texture? in Chapter 5 which is the C balance and the amount of crop residue needed to maintain a stable C balance in a Latosol with a medium and clay texture? The experimental design was a completely randomized 2x2x2 factorial with 12 treatments. Treatments consisted of: a) an Oxisol (Red Latosol) with medium and clayey texture, b) two soil sampling periods (T1 and T2) with one year interval between them, and c) two soil sampling depths (0-5 and 5-20 cm). The soil attributes assessed were: the separation of water stable aggregates classes (19-8, 8-4, 4-2, 2-1, 1-0,5 and 05-0,25 mm), particulate organic carbon (POC), total particulate nitrogen (TPN) in the aggregate classes. Also was determined total organic carbon (TOC) and total nitrogen (NT) in the whole sample and in the aggregates sizes classes and tensile strength of aggregates. The relationship of stratification was calculated by dividing the TOC and TN values of 0-5 cm layer by the values of the same attributes of 5-20 cm layer. The C sequestration rate and the stratification ratio changes were calculated by the difference between the T2 values minus T1. The tensile strength was measured in soil aggregates and assessed in 1920 aggregates for each sampling time. Also TOC and NT content were measured in aggregates. The aggregates greater than 8 mm represented more than 70 of the total mass in both the clay and in sandy soil. The relationship of stratification ratio (0-5:5-20 cm) of SOC, TN, POC and TPN soil indicated the improvement of the surface layer. A significant linear relationship between the SR and C sequestration rate in both textural classes showed an increase in C sequestration and was more evident in LV with medium texture. The increase in TOC content resulted in decreased tensile strength (TS) of the aggregates and was more evident in the 0-5 cm layer. The TS showed inverse relationship with the soil density and was higher in the LV medium texture. The rate of sequestration of C was 0.86 for the LV with medium texture and 0.76 Mg ha-1 for the clay texture and to maintain the stable balance of C is required an input of 8.6 Mg ha-1 of crop residues. The results presented confirm the hypothesis of SR to be a sensitive indicator for the rate of carbon sequestration in no-tillage soil. Key-words: Carbon stock, Carbon balance, Carbon sequestration, Soil management systems, particulate organic carbon, particulate nitrogen.
Keywords: relação de estratificação; taxa de seqüestro de C; plantio direto; Carbono; argila; densidade do solo; carbon stock; carbon balance; carbon sequestration; soil management systems; particulate organic carbon; particulate nitrogen; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA